PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA PADA SISWA KELAS V SDN 2 KRANDEGAN OLEH: HENI NURHAYANTI 1, SURIPTO 2, IMAM SUYANTO3 PGSD FKIP, UNIVERSITAS SEBELAS MARET, JL. KEPOD - NURHAYANTI, HENI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Realistic Mathematics Education Approach Using Visual Media in Improving Mathematics Learning for the Fifth Grade Students of SD Negeri 2 Krandegan. The objectives of this research are to improve Mathematics learning in the fifth grade students of SDN 2 Krandegan. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 32 students of the fifth grade of SDN 2 Krandegan in academic year 2015/2016. Techniques of collecting data were observation, interview, and tests. Validity of data in this research was analyzed using triangulation of technique and sources. Data were analyzed using quantitative and qualitative analysis. The conclusion of this research is the application of Realistic Mathematic Education (RME) approach using visual media can improve Mathematics learning for the fifth grade students of SDN 2 Krandegan in academic year 2015/2016. Keywords: RME, visual media, MathematicsAbstrak: Penerapan Pendekatan Pendidikan Matematika Realistik dengan Media Visual dalam Peningkatan Pembelajaran Matematika pada Siswa Kelas V SDN 2 Krandegan. Tujuan penelitian ini yaitu untuk meningkatkan pembelajaran Matematika pada siswa kelas V SDN 2 Krandegan. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN 2 Krandegan tahun ajaran 2015/2016 yang berjumlah 32 siswa. Teknik pengumpulan data berupa observasi, wawancara, dan lembar soal. Teknik uji validitas data menggunakan triangulasi teknik dan triangulasi sumber. Teknik analisis data menggunakan teknik analisis data kuantitatif dan analisis data kualitatif. Simpulan penelitian ini adalah penerapan pendekatan PMR dengan media visual secara tepat dapat meningkatkan pembelajaran Matematika pada siswa kelas V SDN 2 Krandegan Tahun Ajaran 2015/2016 Kata kunci: PMR, media visual, Matematika